HUBUNGAN ANTARA KONFLIK PERAN GANDA DENGAN STRES KERJA PADA KARYAWATI DI CV. SEMOGA JAYA SAMARINDA - ., Benyamin (MOTIVASI, 2013)
Participation ofwomen todayis not justahousewifealone butmanywomenwhochooseto workoutside the homein an effortto helpthe economy ofthe familyorbecause they want tohonetheir skills. in this caseis no exceptionto theemployeein the CV. Hope fully Jaya Samarinda ispartlyemployee consciousmarriedorwillnotconflicteitherin the familyorworkenvironmentThis study aimstodetermine the relationship ofthe dual roleconflictwithemployeework stresson the CV. HopefullyJayaSamarinda. Thisresearchsubjectisan employee ofCV. HopefullyJaya100employee. Datawere collectedwith adual roleconflictscaleandjob stress. The data analysisusingstatisticalanalysisproduct moment correlation with SPSS version18.0 for Windows.Throught the test responden masa kerja,hasil uji asumsi,hasil uji lineritas,we can know about to determine of the relationship of the dual role conflict with employee work tress on the CV. Semoga Jaya SamarindaThe Results of this studyshowed that therewas significant positivecorrelationbetweenthe dual roleconflictwithjob stressonemployeeCV. HopefullyJayaSamarindato the value ofR=0283andp=0.000.